Use in the studies of physical culture of east single combats as to the means of forming of motivation to the healthy way of life and self-perfection of personality of students - Гаврилюк [Gavrilyk V.] Валерій Олексійович; Опанасюк [Opanasiuk F.] Федір Григорович (Slobozhanskyi Herald of Science and Sport, 2012)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> The article demonstrates the effect of application of martial arts on PE classes (on the example of my method with elements of taekwondo) on formation of motivation to health way of life and self-improvement of personality of the students. The described general concepts on treating methods of Eastern countries, their meaning in the life of people, preservation and strengthening of health, physical development. The introduced academic program in Physical Education (Chapter «Taekwondo») as an alternate part in teaching Physical Education in 8th–9th grades of all types of secondary education schools of 1st–3rd levels. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>